Building sustainable societies through human-centred human resource management: emerging issues and research opportunities. Issue 1 (17th January 2022) - Cooke, Fang Lee; Dickmann, Michael; Parry, Emma
Abstract: In this paper, we argue that adopting a human-centred approach to human resource management (HRM) will contribute to building sustainable workforces, organizations, communities and societies against a backdrop of a global pandemic and political and economic uncertainty. The economic and social cost of the pandemic will continue to be felt for years to come, and the road to recovery should be human-centred and sustainable, with built-in climate actions as part of the socio-economic rejuvenation programme. We draw on several cross-cutting themes to illustrate how the use of digital technology and how remote working, for example, may impact workers from different socio-economic backgrounds in diverse ways. We call for researchers to engage in in-depth qualitative research to identify new phenomena related to work and HRM in the context of accelerating adoption of digital technology and post-Covid recovery to explore power dynamics and forms of exclusion in the labour market and workplaces. Findings of these studies can contribute to positive policy actions to prevent the exacerbation of existing socio-economic inequality and exclusion. They will also contribute to new ways of conceptualizing HRM models and practices and extending HRM theories.